43‐3: Ab‐initio Simulation of Doped Injection Layers. Issue 1 (25th September 2020) - Symalla, Franz; Fediai, Artem; Armleder, Jonas; Kaiser, Simon; Strunk, Timo; Neumann, Tobias; Wenzel, Wolfgang
Abstract : Optimization of doped injection layers in state‐of‐the‐art OLEDs via experimental trial&error by tuning host‐dopant combinations/concentrations is time‐consuming and costly. We present a multiscale‐simulation approach to investigate doping on microscopic level, i.e. the impact of microscopic properties on doping performance, and illustrate how to apply simulations towards materials design.